ARTI PENTING COMMON HERITAGE OF MANKIND DALAM REZIM PENGATURAN AREA DAN PERKEMBANGANNYA [The Importance of the Common Heritage of Mankind Principle in the Regulation of the Area Regime and Its Development] - Agustina Merdekawati; Marsudi Triatmodjo; Irkham Afnan Trisandi Hasibuan; Vivin Purnamawati; Nahda Anisa Rahma (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
UNCLOS 1982 adopted the Common Heritage of Mankind (CHM) principle for the newly established Area regime. The Area regime governs the utilization of the minerals in the deep seabed and ocean floor and the subsoil thereof beyond the limits of national jurisdiction. The CHM principle requires the utilization of the Area to be carried out for the benefit of all mankind. There is no universally agreed-upon definition and scope of the CHM principle, even within the law of the sea sector. The utilization activities in the Area will soon expand to the use of genetic resources, which poses the question on whether the CHM principle should also apply. This research attempted to find the core philosophy of the CHM principle, independent from the UNCLOS 1982 provisions, to better understand its scope and meaning, and how it may impact our understanding of the Area regime. This study is normative legal research and utilized secondary data. The study concluded that the CHM principle has its roots from the res communis, adopted in response to the inability of the latter to ensure fair access to natural resources. The principle has its own independent character outside of UNCLOS 1982 and may be applied to govern the utilization of genetic resources outside states’ jurisdiction under a dedicated international legal instrument. Bahasa Indonesia Abstrak: Kehadiran UNCLOS 1982 membawa pembaharuan dalam hukum laut internasional dengan mengadopsi prinsip Common Heritage of Mankind (CHM) dalam rezim pengaturan baru untuk Area. Rezim pengaturan Area berlaku terhadap pemanfaatan sumber daya mineral pada dasar laut dan lapisan tanah di bawahnya yang berada di luar batas-batas wilayah yurisdiksi negara. Prinsip CHM mengatur bahwa aktivitas pemanfaatan harus membawa kemanfaatan bagi seluruh umat manusia. Masih terdapat perbedaan pendapat mengenai definsi dan lingkup prinsip CHM bahkan dalam konteks hukum laut. Perkembangan pemanfaatan Area mencakup sumber daya genetik menimbulkan pertanyaan mengenai sejauh mana sumber daya dapat disebut suatu CHM. Penelitian ini mengkaji filosofi dari prinsip CHM di luar konteks UNCLOS 1982 untuk memperdalam pemahaman atas prinsip tersebut dan dampaknya terhadap pemahaman pengaturan Area. Penelitian ini merupakan penelitian hukum normatif, dengan menggunakan data sekunder. Hasil penelitian menyimpulkan bahwa prinsip CHM berakar dari konsep res communis yang didorong oleh keinginan untuk menciptakan keadilan akses terhadap sumber daya alam. Sebagai konsep yang independen dari UNCLOS 1982, prinsip CHM dapat diterapkan terhadap sumber daya genetik di luar yurisdiksi negara di bawah instrumen hukum internasional tersendiri.